Seismic fragility analysis of shield building considering strength ratio of mainshock and aftershocks - Xue Zhang; Chunfeng Zhao; Lunhai Zhi; Rui Pang; Y.L. Mo (Nuclear Engineering and Technology, 2024)
The shield building of the AP1000 nuclear power plant serves as a crucial protective barrier against radioactive substances. However, past research indicates that structures are susceptible to experiencing aftershocks, which may lead to unforeseeable damage and potential radioactive material leakage. To address this issue, a finite element model of the shield building was established with the damage indexes of the tensile and compressive damage selected for further model analysis. According to the fundamental theory of reliability, the traditional incremental dynamic analysis method was used to analyze the seismic fragility of the shield building by inputting mainshock and aftershock sequences with three strength ratios. The results indicate that the seismic fragility of shield building may be underestimated without considering the influence of aftershocks and the damage state presents an upward tendency as the strength ratio increases. However, the cumulative damage caused by aftershocks is unlikely to exceed the initial damage induced by the corresponding mainshock. Overall, the aggravation of the compressive damage is less pronounced than the increase of the tensile damage as the strength ratio increases.